Reframing the ‘South’: Divisions of the Globe and British Geographical Imaginations in the Victorian and Edwardian Era - Daniel Foliard (Cahiers Victoriens et Edouardiens)
The idea of the South, conceptualized as a global geo-economic entity, is very recent. It imposed itself very gradually upon British and European geographical imaginations. The world was not divided along a North/South division in the 19th century. Most atlases and general maps published in London or Edinburgh in the late nineteenth century represented the earth along a longitudinal divide. This framework reflected deep-rooted cultural legacies dating back to the Renaissance. It took a paradigm shift in the early twentieth century and major political and scientific evolutions to witness the emergence of new categorizations. Halford Mackinder’s new political geography, constructive imperialism’s emphasis on the notion of development, the birth of international law and the structuration of the field of geopolitics all contributed to foster a new understanding of the world’s balance. This article sets out to demonstrate how these shifting British views of the world echoed wider cultural processes.